Phosphorylations of serines 21/9 in glycogen synthase kinase 3α/β are dispensable for V600EBRAF-driven premalignant tumour development in the mouse intestine - Pooyeh Farahmand; Paulina Rzasa; Caleb Green; Fiona Hey; Susan Giblett; Hong Jin; Kevin West; Nicolas B. Sylvius; Catrin A. Pritchard; Alessandro Rufini (PLoS ONE, 2026)
Valine to glutamate substitution at residue 600 of the BRAF oncogene ( V600E BRAF mutation) is prevalent in human colorectal cancers with a serrated histopathology and is thought to be a founder mutation. Using a conditional knock-in mouse model we have previously demonstrated that V600E Braf drives crypt hyperplasia in the short term as well as shortened survival linked to increased tumour burden in the long-term. These phenotypes are associated with induction of gene signatures for E2F targets, MYC signalling, G2/M transition, canonical Wnt signalling, and cholesterol biosynthesis. Although these gene signatures are reverted by MEK inhibition, there remains a lack of understanding of the signalling pathways involved, particularly the mechanism of crosstalk between the MAPK and Wnt pathways. Here, we have examined a role for phosphorylation of GSK3αβ isoforms at residues S21/S9. By introducing homozygous knock-in mutations for Gsk3αβ S9A/S21A onto the V600E Braf background, we unexpectedly show a marginal effect of these mutations on further increasing crypt proliferation. However, this impact is lost in the long-term as there are no significant differences in mouse survival, tumour burden or tumour grade. Consistently, the Gsk3αβ knock-in mutations do not change the transcriptional programme induced by V600E Braf , except for 3 genes ( Ephx4 , Eif2b3 Ppp1r13l ) whose expression is significantly altered, potentially contributing to the short-term increase in crypt hyperplasia. Overall, our data show that therapeutic strategies targeting GSK3αβ phosphorylation at serines 21/9 are not worthwhile options for V600E BRAF colorectal cancers.